Challenge of Drosophila melanogaster with Cryptococcus neoformans and Role of the Innate Immune Response - Apidianakis, Yiorgos (American Society for Microbiology, 2004)
We found that the ingestion of Cryptococcus neoformans by Drosophila melanogaster resulted in the death of the fly but that the ingestion of Saccharomyces cerevisiae or the nonpathogenic Cryptococcus kuetzingii or Cryptococcus laurentii did not. The C. neoformans protein kinase A and RAS signal transduction pathways, previously shown to be involved in virulence in mammals, also played a role in killing Drosophila. Mutation of the Toll immune response pathway, the predominant antifungal pathway of the fly, did not play a role in Drosophila defense following ingestion of the yeast. However, the Toll pathway was necessary for the clearance of C. neoformans introduced directly into the hemolymph of D. melanogaster and for the survival of systemically infected flies.